(untitled) (The Review of Diabetic Studies, 2024)
Background Healthcare-associated infections (HAIs) represent a pervasive and escalating challenge to global health security, affecting between 3.6% and 8.0% of hospitalized patients worldwide. While the etiology of HAIs is multifactorial, the intersection of human behavior, institutional policy, and environmental infrastructure remains the primary determinant of transmission. Historically, infection prevention and control (IPC) surveillance has predominantly focused on nursing and medical staff, leaving the compliance behaviors of allied technical teams—specifically dentistry personnel and operation technicians (surgical technologists and sterile processing staff)—under-represented in the epidemiological literature. This gap is critical, as these groups manage high-risk vectors including aerosolized pathogens and invasive surgical instrumentation. Objective This systematic review aims to synthesize epidemiological data regarding IPC compliance across three distinct healthcare cadres: Nursing, Dentistry, and Operation Technician teams. The primary objectives are to: (1) compare quantitative compliance rates across these specialties; (2) identify specialty-specific failure modes, distinguishing between behavioral, cognitive, and systemic barriers; and (3) evaluate the efficacy of the World Health Organization (WHO) Multimodal Improvement Strategy versus standard educational interventions in these diverse operational contexts. Methods A comprehensive systematic review was conducted adhering to the PRISMA 2020 guidelines. Data sources included PubMed, EMBASE, Cochrane Library, and WHO/CDC technical reports published between 2000 and 2024. The review included randomized controlled trials, observational cohort studies, and cross-sectional surveys. Quality assessment was rigorous, utilizing the Newcastle-Ottawa Scale (NOS) for observational studies and the Cochrane Risk of Bias 2.0 (RoB 2) tool for interventional studies. Data synthesis focused on extracting compliance percentages, odds ratios for adherence, and qualitative themes related to psychosocial and environmental barriers. Results The analysis of 124 distinct data sources reveals significant variance in compliance drivers and failure mechanisms. Nursing compliance with hand hygiene varies widely (45-65%) and is strongly negatively correlated with burnout and "effort-reward imbalance." In contrast, dental teams demonstrate high theoretical knowledge (93% conceptual accuracy) but suffer from "process-driven non-compliance," particularly regarding environmental disinfection and instrument turnover times. Operation technicians exhibit a distinct risk profile: while surgical technologists in the operating room maintain high vigilance for sterile field breaches, sterile processing technicians in decontamination units face a "visualization crisis," with 88% of instrument defects attributed to visual inspection failures under high production pressure. The cumulative risk of error in sterile processing was quantified at 4.8 defects per instrument set. Conclusion Institutional IPC is not a monolithic challenge solvable by generic education. Compliance is highly role-specific: nursing requires psychosocial support to combat fatigue; dentistry requires process engineering to manage turnover pressure; and operation technicians require advanced visualization technology to overcome human cognitive limitations. The WHO Multimodal Strategy is superior to single-mode interventions but must be adapted to address the specific "epidemiology of work" within each specialty. Strengthening IPC requires a shift from blaming individuals to engineering resilient systems that account for the unique stressors of each healthcare domain.